Zeeman effect on surface electron transport in topological insulator Bi2Se3 nanoribbons. Issue 40 (24th September 2015) - Wang, Li-Xian; Yan, Yuan; Zhang, Liang; Liao, Zhi-Min; Wu, Han-Chun; Yu, Da-Peng
Abstract : The effect of topological insulator surface states' spin and orbital angular momentum on transport under an in-plane magnetic field is studied. Abstract : Topological insulators have exotic surface states that are massless Dirac fermions, manifesting special magnetotransport properties, such as the Aharonov–Bohm effect, Shubnikov–de Haas oscillations, and weak antilocalization effects. In the surface Dirac cone, the band structures are typically closely related to the p-orbitals and possess helical orbital texture. Here we report on the tunability of the transport properties via the interaction between the magnetic field and the spin–orbital angular momentum of the surface states in individual Bi2 Se3 nanoribbons. Because the surface states have a large Landé factor and helical spin–orbital texture, the in-plane magnetic field induced Zeeman energy will result in the deformation of the Dirac cone, which gives rise to spin polarization of the surface states. The spin-dependent scattering of the conducting electrons on the existing local magnetic moments produces a giant negative magnetoresistance. The negative magnetoresistance is robust with a ratio of −20% at 2 K and −0.5% at 300 K under 14 T. The results are valuable for possible orbital-electronics based on topological insulators.